STRUKTUR DAN KOMPOSISI VEGETASI MANGROVE DI DESA BANGKAGI KECAMATAN WALEA KEPULAUAN KABUPATEN TOJO UNA UNA - Mahdar Y. Aswadi; Ramadhanil Ramadhanil; Samsurizal M. Suleman (Biology Department, Mathematics and natural science, Tadulako University, 2014)
A research on the structure and composition of mangrove vegetation in the Bangkagi Village South Walea Tojo Una Una District has been conducted from September to October 2013 which aims to determine the structure and composition of mangrove vegetationin the studied area. The research was used exploratory survey method by using line (transect method) and in thetransects, plots were made in the size 10 m x 10 m for the observation of trees,5 m x 5 m for the poles and the 2 m x2 m for seedlings.The result of the research showed that there were 7 species of mangrove namely: Ceriopstagal, Avicennia marina, Sonneratia alba, Rhizophora mucronata, Bruguiera gymnorhia, Xylocarpus molluccensis and Schiphyphora hydrophillacea. It’s belong to 5 family that Rhizophoraceae, Avicenniaceae, Sonneratiaceae, Meliaceae and Rubiaceae. The diversity index of Mangrove species at Bangkagi village was low. Species Mangrove of trees in the studied area were dominated by Rhizophora mucronata (193,63%),mean while Rhizophora mucronata (173,30 %) and Rhizophora mucronata were dominant on the level of sapling and seedling (135,35 %). Keywords :Structure, Composition, Mangrove, Bangkagi village.